Breast cancer survival in New Zealand women. Issue 7 (29th September 2014) - Campbell, Ian D.; Scott, Nina; Seneviratne, Sanjeewa; Kollias, James; Walters, David; Taylor, Corey; Webster, Fleur; Zorbas, Helen; Roder, David M.
Abstract: Background: The Quality Audit (BQA) of Breast Surgeons of Australia and New Zealand includes a broad range of data and is the largest New Zealand (NZ) breast cancer (BC) database outside the NZ Cancer Registry. We used BQA data to compare BC survival by ethnicity, deprivation, remoteness, clinical characteristic and case load. Methods: BQA and death data were linked using the National Health Index. Disease‐specific survival for invasive cases was benchmarked against Australian BQA data and NZ population‐based survivals. Validity was explored by comparison with expected survival by risk factor. Results: Compared with 93% for Australian audit cases, 5‐year survival was 90% for NZ audit cases overall, 87% for Maori, 84% for Pacific and 91% for other. Conclusions: BC survival in NZ appears lower than in Australia, with inequities by ethnicity. Differences may be due to access, timeliness and quality of health services, patient risk profiles, BQA coverage and death‐record methodology.